Grid connected photovoltaic system efficiency and quality improvement using fuzzy-incond MPPT - Amara Yasmine; Bradai Rafik; Boukenoui Rachid; Mellit Adel (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Maximum Power Point Tracking (MPPT) techniques are developed to harvest and supply maximum power to the load. This depends on the power generated and the MPPT accuracy. Under quick-changing weather conditions, Incremental Conductance (InCond) and numerous different algorithms may fail to track the exact Maximum Power Point (MPP) which may result in significant power loss. Fuzzy Logic (FL) based MPPT is quick and accurate in tracking the MPP, but the high complexity and the implementation difficulty are their main disadvantages. A novel FL-InCond MPPT improved technique is developed based on the features of InCond and FL techniques to overcome their drawbacks.The newly developed approach can automatically adjust the variation of the duty cycle for tracking the MPP with accuracy. The obtained results are compared with conventional Perturb and observe (P&O) and InCond MPPTs for grid-connected mode under fast weather conditions. It is demonstrated that the developed method outperforms the aforementioned MPPT techniques in terms of tracking response, efficiency and the delivered current quality.